Having Too Much: Philosophical Essays on Limitarianism - Ingrid Robeyns (Open Book Publishers, 2023)
Having Too Much is the first academic volume devoted to limitarianism: the idea that the use of economic or ecosystem resources should not exceed certain limits. This concept has deep roots in economic and political thought. One can find similar statements of such limits in thinkers such as Plato, Aquinas, and Spinoza. But Having Too Much is the first time in contemporary political philosophy that limitarianism is explored at length and in detail. Bringing together in one place the best writing from key theorists of limitarianism, this book is an essential contribution to political philosophy in general, and theories of distributive justice in particular. Including some of the key published articles as well as new chapters, Having Too Much is necessary reading for scholars and students of political theory and philosophy, as well as anyone interested in questions of distributive justice.
Keywords: 320; limitarianism; material resources; economic limitarianism; ecological limitarianism; future generations; political thought; distributive justice; intergenerational justice